2020
DOI: 10.1088/1361-665x/ab83cd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes on the in-plane dynamic behavior of a carbon/epoxy composite under high strain rate compression using SHPB

Abstract: Fiber reinforced composites have wide structural applications and vast research has been going on to improve their mechanical performance when subjected to quasi-static loading but, study of their dynamic behavior is still underdeveloped. For this reason, scientists have been continuously working on developing methods to improve their dynamic characteristics and addition of nanofillers suchs as Carbon Nanotubes (CNTs) as reinforcement is considered a possible solution for developing future generation high-qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To date, most studies found in the literature that were carried out on the dynamic mechanical properties of composite materials revolved around thermosetting composites [ 15 , 16 , 17 , 18 , 19 , 20 ] and compressive behavior [ 20 , 21 , 22 , 23 ]. Unlike the more commonly used thermoplastic composites that were reinforced with glass fibers [ 24 ], short fibers [ 25 ], basalt fibers [ 26 , 27 ]; very limited information can be found on in the literature on the dynamic properties, specifically, dynamic tensile properties of continuous carbon fiber-reinforced polymer (CFRP) composites [ 28 , 29 , 30 , 31 ], let alone the more recent carbon fiber-reinforced thermoplastic (CFRTP) composites [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies found in the literature that were carried out on the dynamic mechanical properties of composite materials revolved around thermosetting composites [ 15 , 16 , 17 , 18 , 19 , 20 ] and compressive behavior [ 20 , 21 , 22 , 23 ]. Unlike the more commonly used thermoplastic composites that were reinforced with glass fibers [ 24 ], short fibers [ 25 ], basalt fibers [ 26 , 27 ]; very limited information can be found on in the literature on the dynamic properties, specifically, dynamic tensile properties of continuous carbon fiber-reinforced polymer (CFRP) composites [ 28 , 29 , 30 , 31 ], let alone the more recent carbon fiber-reinforced thermoplastic (CFRTP) composites [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of micro and macro thermodynamic tests, it was revealed the influence of CNTs content changes on the thermodynamic properties of the novel nanocomposite. Some of the conclusions of this article can be supported by the research of Tarfaoui et al [41][42][43]. By introducing carbon nano reinforced fillers into the TPI/HDPE hybrid matrix, it can not only expand the application range of carbon nanofillers, but also provide potential technical reference for the application of novel cardiac stent, functional gypsum, composite pipe and pipeline repair engineering in the future [44][45][46][47][48].…”
Section: Introducementioning
confidence: 82%
“…The concept of nanocomposites is based on the control of the dispersion of particles to make the best use of their structural aspects, such as their large specific surface area, allowing many polymer/ particle interactions as well as their high form factor. [11][12][13] The size (nanometric) can offer an enormous specific surface area and significant stability. Therefore, adding nanoparticles within composite materials will broaden their field of application.…”
Section: Introductionmentioning
confidence: 99%